ANALISIS STRATEGI DAN TANTANGAN TUTOR DALAM MENGAJARKAN KETERAMPILAN BERBICARA BAHASA INGGRIS: STUDI TENTANG KURSUS BAHASA INGGRIS BEC - Yoni Yoni; Yelni Erniyati (Universitas Putera Batam, 2026)
This study aims to analyze the strategies and challenges faced by tutors in teaching English speaking skills at the British English Course (BEC) Camp in Sungai Penuh, Kerinci. A descriptive qualitative method was employed, with data collected through observations, semi-structured interviews, and documentation. The participants were two experienced tutors who have been teaching for a minimum of three years. Data were analyzed using thematic analysis to identify key patterns and themes. The findings revealed that tutors employed strategies such as mouth movement training for pronunciation and the implementation of an immersive